Antibacterial Activity ofMiswak(SalvadorapersicaL.)Stem Aqueous and Ethanolic Extracts in vitro - Yahya Dreaim Syhood (College of Pharmacy / Mustansiriyah University, 2018)
The aim was to evaluate the in vitro antibacterial activity of three concentrations (50, 75 and 100 μg/ml) of aqueous and ethanoliccrudeextractsofmiswak(Salvadorapersica) on threepathogenic bacteria (Staphylococcus aureus, Streptococcus pyogenesand Pseudomonas aeruginosa)using agar well-diffusion method.Phytochemical analysis revealed that the extracts contained alkaloids, flavonoids, phenols, tannins and steroids. Antibacterial evaluations demonstrated that both extracts inhibited the growth of the investigated bacteria in a concentration-dependent manner, but the aqueous extract was more efficient than the ethanolicextract.Thehighest growth-inhibition (GI) zone(22.1± 2.3mm)was observed in the culture ofP. aeruginosaat the concentration 100 μg/mlof the aqueous extract, while the lowest (12.3± 1.2 mm) was inthe culture of S.aureus using the ethanolic extract at the concentration 50 μg/ml. These findings suggest the antibacterial potential of Salvadorapersica stem, which might be related to its chemical constituents..